"We're All Victims": Changes in the Narrative of "National Reconciliation" in Argentina. (May 2015) - Salvi, Valentina
While the call for "national reconciliation" as a way to avoid criminal trials for human rights violations has been a constant refrain in the discourse of the armed forces since the return to democracy in Argentina in 1983, it has been made from different positions and in response to diverse conjunctures. Changes in the rhetoric of national reconciliation have been employed as a political and extrajudicial strategy by both the military and civilians for 30 years. The proposal of national reconciliation has oscillated between the need to forget the long-term effects of an "antisubversive war" and a sort of "duty to remember" in which all Argentines are brothers in the evocation of collective pain. Aunque el llamado a la "reconciliación nacional" como una manera para evitar los juicios penales por violaciones a los derechos humanos ha sido un estribillo constante en el discurso de las fuerzas armadas desde el regreso de la democracia en la Argentina en 1983, éste se ha hecho desde diferentes posiciones y como respuesta a coyunturas diferentes. Los cambios en la retórica de la reconciliación nacional han sido usados como una estrategia política y extrajudicial tanto por los militares como por los civiles desde hace 30 años. La propuesta de reconciliación nacional ha oscilado entre la necesidad de olvidar los efectos a largo plazo de la "guerra antisubversiva" y una especie de "deber de memoria" en el que todos los argentinos están hermanados en la evocación de un dolor colectivo.